SISTEM ABSENSI TERINTEGRASI KURIKULUM 13 BERBASIS R+ PADA SDN SUKANAGARA - Febriyanto, Erick; Naufal, Romzi Syauqi; Utomo, Anggit Panji Pangestu (Technomedia Journal, 2020)
In the early history of the development of the system of attendance in Indonesia known as system orally. First, the submission of attendance with oral done by collecting all the members, then the head of the squad going forward before the other employees to mengabsen one by one. If one is not present, then asked what the cause and reason. After the system delivery attendance orally, began to apply paper and media system is still applied in basic education, particularly in the SDN Sukanagara. because it is still present the information with the media system of paper it is need for thoroughness rekapan a comparison to measure attendance information on each subject takes time, whereas its data storage medium using the application Microsoft Excel. Plus, teachers are quite busy with improvements so often forget to fill out the list of absences and less effective for dealing with students who are truant at school subjects. In order to make it easier for the teacher to do recording and measurement of the student's attendance at any course system, teaching and learning-based R + is a system which helps teachers and homeroom present information in the form of absentee form with web feature i.e. can run through mobile. System R + also uses a mobile-based website because of light. The existence of this study it is expected that this attendance system can improve the quality of attendance in the learning process at SDN Sukanagara.